Relevansi Nilai-Nilai Pancasila dalam Era Digitalisasi - Habib Sabila Ihsani (PT. Hasba Edukasi Mandiri, 2025)
Digital transformation has brought about fundamental changes in various dimensions of Indonesian society, including social, political, economic, and cultural aspects. Amidst rapid technological developments, there has been academic concern about the relevance of Pancasila as the philosophical foundation of the nation in responding to challenges in the digital space. This study aims to examine the ability of Pancasila values to adapt and serve as ethical guidelines in the digital age. Through a descriptive qualitative approach using literature study and document analysis methods, the results of this study reveal that Pancasila has high relevance in overcoming contemporary issues such as digital ethics, cyberbullying, the spread of disinformation, hate speech, and technological access gaps. The five principles of Pancasila offer philosophical guidance for the wise use of technology, while also establishing a digital ethical framework based on the values of divinity, humanity, unity, democracy, and justice. To realize this, synergistic collaboration between stakeholders, including the government, educational institutions, digital platform providers, and the general public, is needed to create a digital ecosystem that is not only productive but also has integrity and upholds the dignity of the nation.